Toward improving the quality compliance checking of urban private constructions in Iran: An ontological approach. (April 2018) - Moradi, Hossein; Sebt, Mohamad Hassan; Shakeri, Eghbal
Abstract: City, as a complex system, needs to be managed as an integrated entity so that every encumbrance that slows its processes could be eliminated. However, developing a single mature model to integrate the whole processes of the various systems in the city is not practical. Yet, it is possible to develop purposeful and consistent models, for each specific system, that all together eventuate in the integrated management. In this regard, the mechanism of constructions quality compliance checking is one out of many systems in Iran that needs to be addressed for integration due to three main reasons; first, the multiplicity of problems in this section; secondly, the multidimensional significance of this section; and finally the ability to improve the status quo through using appropriate approach. Accordingly, the present study, by developing an ontology, which is named QA-ontology, as a missing chain, and using existent ontologies in previous studies, presents a conceptual model. This model takes advantages of the ability of ontologies in the information storing as a graph. This type of information storing provides the homogeneous information that is needed for both integration in the quality compliance checking of urban private constructions and assimilation into further extensions of integration in other mechanisms of a city.